Supply Chain Flexibility Evaluation Based on Matter-Element Extension. (20th May 2020) - Luo, Xiaochun; Wang, Zilong; Lu, Lin; Guan, Yan
Abstract : Flexibility is an important indicator to consider the uncertain information processing ability of the supply chain comprehensively. It is a powerful way to improve the efficiency and quality of supply chain operation by evaluating the level of supply chain flexibility effectively. The traditional method is used to decompose the supply chain flexibility evaluation indicators from the perspective of system structure or cost saving, but these indicators cannot truly describe the dynamics of the supply chain operation. Otherwise, supply chain flexibility evaluation is a typical multiobjective evaluation; there are some incompatibilities between these flexible evaluation indicators, and the common evaluation methods are difficult to deal with such contradictions. In this paper, the dynamic characteristics of supply chain operation are considered, and the evaluation system of supply chain flexibility is designed from the perspective of operation efficiency. The matter-element analysis theory is used to create the comprehensive appraisal model of supply chain flexibility. The matter-element matrix solves the uncertainty and incompatibility of the evaluated factors used to assess supply chain flexibility. The paper evaluates the performance of four autoservice companies and concludes that the evaluation grades of the four companies are in line with the reality, indicating that the evaluation system and the method are effective and credible.